Case Study: Implementation Of Presidential Instruction Number 7 Of 2025 And Community Synergy In Gresik Regency - Dwi Ardiyanti; Sri Rahayu Maulidah Maskurina (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to analyze the implementation of Presidential Instruction Number 7 of 2025 concerning the acceleration of educational digitalization and community synergy in supporting its implementation in Gresik Regency. The study used a qualitative approach with a case study design to gain a deep understanding of the phenomenon under study. Data were collected through in-depth interviews, observations, and documentation studies, then analyzed using an interactive analysis model at SMAN 1 Wringinanom and SMAN 1 Balongpanggang, as the research samples. The results explain that the implementation of the educational digitalization policy has been ongoing, but has not been optimal due to limited technological infrastructure, variations in the digital competencies of educators, and budget constraints. Furthermore, community synergy has proven to be crucial in supporting the policy's success, although there remains a gap in participation between urban and rural areas influenced by digital literacy, technology access, and economic conditions. This study also found that the success of the policy's implementation is largely determined by collaboration between the government, educational institutions, and the community through a collaborative governance approach, although this collaboration is still in its infancy. Therefore, strengthening infrastructure, improving digital competencies, and developing a more systematic collaboration model are needed to increase the effectiveness of the educational digitalization policy.